2018
DOI: 10.21037/jtd.2017.11.144
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional computed tomography reconstruction for operative planning in robotic segmentectomy: a pilot study

Abstract: Background: The objective of our pilot study was to assess if three-dimensional (3D) reconstruction performed by Visible Patient™ could be helpful for the operative planning, efficiency and safety of robotassisted segmentectomy. Methods: Between 2014 and 2015, 3D reconstructions were provided by the Visible Patient™ online service and used for the operative planning of robotic segmentectomy. To obtain 3D reconstruction, the surgeon uploaded the anonymized computed tomography (CT) image of the patient to the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…11,12 Furthermore, in currently available techniques 3D segmentation (which is the identification and selective coloring of an anatomic structure) is often performed manually (by technicians), which increases the risk for error, requires manual labor, is time-consuming, and for this reason is more expensive. 18 Another shortcoming of the available 3D modeling software is that it commonly requires contrast-enhanced CT scanning for accurate segmentation, which results in radiation and iodinecontrast agent exposure and consequently in additional health risks for patients. 18 In this study, we have demonstrated that our PulmoVR application provides a unique environment to review patient-specific segmental anatomy by facilitating selective AI-based automatic labeling, visualization, and assessment of pulmonary structures, without the need for contrast-enhanced CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Furthermore, in currently available techniques 3D segmentation (which is the identification and selective coloring of an anatomic structure) is often performed manually (by technicians), which increases the risk for error, requires manual labor, is time-consuming, and for this reason is more expensive. 18 Another shortcoming of the available 3D modeling software is that it commonly requires contrast-enhanced CT scanning for accurate segmentation, which results in radiation and iodinecontrast agent exposure and consequently in additional health risks for patients. 18 In this study, we have demonstrated that our PulmoVR application provides a unique environment to review patient-specific segmental anatomy by facilitating selective AI-based automatic labeling, visualization, and assessment of pulmonary structures, without the need for contrast-enhanced CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical value of the 3D model was validated in 2014 in a pilot study (6). Progressively, we have reached the conclusion that the availability of such Figure 1 Flow chart of the implementation of our robotic technique of segmentectomy reinforced by our multimodal imaging system (5-7).…”
Section: Experiencementioning
confidence: 91%
“…3D reconstruction (Visible Patient TM ) for preoperative planning Pilot Study (6) 2013-2015 3D reconstruction for pre-operative planning and intraoperative real-time imaging 2016-2017 3D reconstruction and Pleural dye marking for certain tumor location (7) 2016-2017…”
Section: Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Pre-operative CT chest with 3D reconstruction can be extremely helpful to become familiar with the segmental anatomy and identify the branches of the vein, pulmonary artery, and bronchus to the particular segment. This also allows the surgeon to decide if segmentectomy would be an adequate oncological resection (31,32). Pre-operative localization of the smaller deeper nodule can be helpful for intra-operative identification of the lesion.…”
Section: Pre-operative Planning For Robotic Segmentectomymentioning
confidence: 99%